Monitoring of reproductive health in the striped catfish Pangasianodon hypophthalmus (Sauvage, 1878) from the Saen Saep Canal, Thailand - Thawanrat Puttipong; Sinlapachai Senarat; Jes Kettratad; Chitchai Chantangsi; Tassaporn Kanjanarakha (Veterinary Integrative Sciences, 2021)
Khlong Saen Saep is one of the most important and large canal systems in Bangkok, Thailand. However, the emergence of heavily polluted water has occasionally been reported due to the domestic sewage and industrial effluents discharged into the system. This situation may affect the reproductive status of aquatic lives residing in this canal. To evaluate the reproductive status of the canal inhabitant, the striped catfish Pangasianodon hypophthalmus (Sauvage, 1878)—a common dweller of the Saen Saep Canal—was collected from two selected stations, the Bumpen Nua Temple and the Kamalun Islam Mosque. The fish gonads were then anatomically and histologically examined. The results indicated that neither parasites nor ovary with external abnormality were found. Nevertheless, several histological alterations were detected, including vacuolar degeneration of previtellogenic oocytes, accumulation of melanomacrophage centers (MMCs), and atretic oocytes. Moreover, severe histopathological changes, such as the eosinophilic cytoplasm of spermatogonia, MMCs, blood congestion, and syncytium of spermatozoa, were observed in the fish testis. Our study suggested that the environmental stress and pollutions previously reported from the Saen Saep Canal possibly underpin the gonadal impairments of P. hypophthalmus examined and may have adverse impact on the reproductive health of others living in this canal system